STUDI DIAGENESA DAN PENGARUHNYA TERHADAP PERKEMBANGANPOROSITAS BATUGAMPING FORMASI RAJAMANDALA DAERAH BANCANA,MASIGIT, GUA PAWON - Aribowo, Yoga
Rajamandala Formation Limestone was formed in Late Oligocene – Early Miocene. During the geological history since it deposited, Rajamandala Formation had influenced by many geological processes, include diagenesis. The diagenesis processes begin at time the sediment deposited until recent. About 42 samples taken from location to be analyzed petrographicaly to identify carbonate facies distribution and to analyze diagenetic processes reflected on the cement morphology, textural features and cross cutting relationship among the textural constituents. From the field data and petrographic analysis, carbonate facies in Bancana, Masigit,and Guapawon are consist of foraminifera - red algae packstone in the lower part, platy coral bindstone –framestone in the middle part, and the upper part consist of foraminifera packstone-wackestone and coral rudstone. Marine diagenetic feature observed in the petrographic study are micritic envelope, fibrous isopach cement and cement filling inside grain. Vadose meteoric diagenetic feature that observed are pendant cement/meniscus and the skeletal dissolution. Fresh water phreatic diagenetic feature are isopach equant cement as neomorphism product from fibrous aragonite, and pore filling by blocky calcite cement. Burial diagenetic feature that observed are grain fracture, stylolite, and drusy mosaic spar. Primary porosity not developed, but secondary porosity well developed with average porosity about 1-2% as vugy, channel and intercrystaline porosity. Another diagenetic feature observed is dolomitization that may be formed in burial or mixing of fresh water-marine phreatic environment.